2019
DOI: 10.5713/ajas.18.0610
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and sensory characteristics of commercial, frozen, dry, and wet-aged Hanwoo sirloins

Abstract: Objective The objective of this study was to evaluate the physicochemical, sensory and taste characteristics of commercial, frozen, dry, and wet aged Hanwoo sirloin. Methods Grade 2 sirloin from 6 Hanwoo steers (about 30 months old) were obtained after 5 days postmortem . Samples were assigned to four groups which were commercial beef (CON, control group), frozen beef (Hanwoo frozen, HF; 40 days in −18°C freezer), wet-aged beef (Hanwoo wet-agi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 30 publications
3
13
1
Order By: Relevance
“…Aksu et al [14] reported that the increase in pH during aging process is because of the formation of nitrogen compounds from proteolysis. In agreement with the results reported by Kim et al [6] we observed that the pH of DAB was higher than that of WAB. The lightness, redness, and yellowness values of DAB were lower than those of WAB (p<0.05), owing to the high pH and WHC of DAB [6].…”
Section: Physicochemical Properties and In Vitro Digestibilitysupporting
confidence: 93%
See 4 more Smart Citations
“…Aksu et al [14] reported that the increase in pH during aging process is because of the formation of nitrogen compounds from proteolysis. In agreement with the results reported by Kim et al [6] we observed that the pH of DAB was higher than that of WAB. The lightness, redness, and yellowness values of DAB were lower than those of WAB (p<0.05), owing to the high pH and WHC of DAB [6].…”
Section: Physicochemical Properties and In Vitro Digestibilitysupporting
confidence: 93%
“…In agreement with the results reported by Kim et al [6] we observed that the pH of DAB was higher than that of WAB. The lightness, redness, and yellowness values of DAB were lower than those of WAB (p<0.05), owing to the high pH and WHC of DAB [6]. In terms of consumer perceptions, higher redness of meat contributes to the increase in meat colour acceptability.…”
Section: Physicochemical Properties and In Vitro Digestibilitysupporting
confidence: 93%
See 3 more Smart Citations